Living on the Edge : Vulnerability to Poverty and Public Transfers in Mexico - de la Fuente, Alejandro; Ortiz-Juárez, Eduardo; Rodríguez-Castelán, Carlos (Taylor and Francis, 2018)
Social policy in Mexico has focused on identifying and supporting households in extreme poverty. Yet, the country has a significant number of households just above the poverty line who are not eligible, by definition, for antipoverty programs and are at risk of falling into poverty in the event of adverse shocks without appropriate social safety nets. This study uses cross-section and longitudinal data to understand better the profile of those ‘vulnerable’ households, their risk exposure, and the extent to which they are covered by public transfers and insurance mechanisms. The analysis shows that until 2010 most social programs, including the few with productive components, barely covered the vulnerable. The study calls for public policies to pay attention to the vulnerable and find a policy mix on the continuum between targeted interventions and universal insurance schemes to serve this income group.